Dietary habits and complex food relations in Northwest China: a population-based network analysis - Xinhua Wang; Duolao Wang; Shaonong Dang; Baibing Mi; Hong Yan; Yuhong Zhang; Yijun Kang; Jianghong Dai; Jing Hui; Samuel Chacha; Huang Yan; Zongkai Li; et al. (BMJ Nutrition, Prevention & Health)
Introduction This study examines dietary network in Northwest China, focusing on food group consumption and regional trends using network analysis.Methods Data from 106 424 participants in the Regional Ethnic Cohort Study were calculated using a semiquantitative food frequency questionnaire. We compared intake with the 2022 Chinese Dietary Guidelines and employed the EBICglasso method to construct dietary and staple food-related network, assessing its stability and accuracy.Results Northwest China’s staple food intake was 37.5% of total consumption, dominated by wheat. Compared with the Chinese dietary guidelines, participants’ intake of staple foods, soybeans and nuts was within the acceptable range, with insufficient intake of whole grains and beans, animal source of foods, eggs, fruits and vegetables but excessive intake of salt. Intake varied by province, sex and age. In overall participants, the strongest correlations were found between the two food groups, namely fruits and vegetables (0.33), and animal source of foods and dairy products (0.24) in dietary network. Soybeans and nuts appeared to connect to more other foods and also higher correlation with other foods and were followed by animal source of food. The staple food-related food network indicated that the intake of rice, whole grains and beans, and potatoes was positively correlated with the intake of most other foods, while intake of wheat was negatively correlated with foods of animal source of food, milk and dairy products.Conclusions Northwest China’s diet exhibits irrational patterns, highlighting the importance of assessing overall dietary patterns in nutritional evaluation.